KETERLIBATAN POLITIK AKTIVIS MAHASISWA MELALUI MEDIA ONLINE - Abdul Gofur; Triyani Triyani (Bhineka Tunggal Ika: Kajian Teori dan Praktik Pendidikan PKn, 2022)
AbstractThe development of online media has an impact on changes access and integration from conventional media to online media. Media digitization also leads to accelerated communication and interactivity as well as changes in political engagement. The purpose of this article is to describe the political involvement of student activists through online media. This type of research uses survey research with a quantitative approach. The population in the study amounted to 651 members who came from the Student Executive Board activists at Yogyakarta State University in 2018. The research sample used was 90 students. Analysis on descriptive statistics is done by determining the frequency distribution, position of numerical scores that represent such as mean, median, and mode. The results of data analysis show that the majority of student activists who seek political news through online media are 40%, the most frequently accessed site is Kompas.Com by 45.6%, political learning media through mass media and organizations by 35.6%. The political themes that are often accessed are related to the change of power, political policies on education, social and economic development with a percentage of 43.3%. The effort to filter the highest information lies in viewing different online mass media channels by 26.7%. Political involvement in the form of writing, audio and video as well as social media with a percentage of 34%. The form of political involvement in the online media space is the majority of writing aspirations using social media with 26.7% of participants.Keywords: Online media, Politics, Student activistsABSTRAKPerkembangan media online berdampak terhadap perubahan akses serta integrasi dari media konvensional kepada media online. Digitalisasi media juga mengarah pada percepatan komunikasi dan interaktivitas serta perubahan  keterlibatan politik. Tujuan artikel ini untuk mendeskripsikan keterlibatan poliitk aktivis mahasiswa melalui media online. Jenis penelitian menggunakan penelitian survey dengan pendekatan kuantitatif. Populasi dalam penelitian berjumlah 651 anggota yang berasal dari aktivis Badan Eksekutif Mahasiswa di Universitas Negeri Yogyakarta pada tahun 2018. Sampel penelitian yang digunakan berjumlah 90 mahasiswa. Analisis pada statistik deskriptif dilakukan dengan menentukan distribusi frekuensi, posisi skor numerik yang mewakili seperti mean, median, dan modus. Hasil analisis data menunjukan mayoritas aktivis mahasiswa yang mencari berita politik melalui media online 40%, situs yang paling sering diakses Kompas.com sebesar 45,6%, media belajar politik melalui media massa dan organisasi sebesar 35,6%. Tema politik yang sering diakses terkait pergantian kekuasaan, kebijakan politik tentang pendidikan, pembangunan sosial dan ekonomi dengan persentase sebesar 43,3%. Upaya untuk menyaring informasi tertinggi terletak pada melihat saluran media massa online yang berbeda sebesar 26,7%. Majalah politik online yang sering dibaca adalah  tempo sebesar 37,8%. Bentuk keterlibatan politik dalam ruang media online mayoritas menulis aspirasi menggunakan media sosial dengan pesertase sebesar 26,7%.Kata Kunci: Media online, Politik, Aktivis Mahasiswa,